(untitled) (Cadernos de Sociomuseologia, 2016)
This article discusses the context, the history and the main achievements of the Museum Afro Brazil. The Unified Black Movement (MNU) was created in 1978 in São Paulo and was considered strongly leftist in orientation and more militant than any of its predecessors. As stated in the text Black Protest in São Paulo, the movement was a strong expression of dissatisfaction among the educated and skilled african-Brazilian denied entering the middle-class status. The Afro Brasil Museum was open on the 23th of October of 2004 as a result of more than two decades of intense research, publications, exhibitions and the dedication of its current director and curator Emanuel Araújo Keywords: Afro Brazil Museum;